알코올중독자 남편을 둔 여성배우자의 자아주체성 회복경험에 대한 현상학적 연구 - 최미란(Mi-Ran Choi); 조희선(Hee-Sun Cho) (한국콘텐츠학회 논문지, 19(3), 2019)
The objective of this study was to evaluate how wives of alcoholics could escape from the co-dependency relationship and recover their ego-subjectivity. This study conducted 1:1 in-depth interviews with five wives of alcoholics in order to achieve the study objective. Data collected from the interviews were analyzed by the phenomenological method proposed by Giorgi[1]. First, researchers extracted five subjects, including 'Co-dependency (Loss of ego-identity)', 'Impoverished life', Ego-prop', Ego-awareness', and 'Ego-subjectivity recovery' in the course of the data analysis. Secondly, researchers identified "Ego-subjectivity recovery through Ego-awareness of a wife of an alcoholic", an essential theme, by integrating all subjects. Researchers, based on the analysis results, proposed practical alternatives for various psychological treatment system and ego-prop like as counselling, family member of alcoholic wives and power of faith. 본 연구의 목적은 여성배우자들이 남편인 알코올중독자와의 공동의존관계에서 벗어나 자아주체성을 어떻게 회복하는가를 탐구하는 것이다. 연구의 목적 달성을 위해 알코올중독자 여성배우자 5인과 1:1 심층면접을 실시했다. 면담을 통해 수집한 자료는 Giorgi[1]가 제안한 현상학적 연구방법으로 분석하였다. 주요 연구결과는 다음과 같다. 첫째, 자료분석과정에서 연구자들은 '공동의존(자아주체성 상실)', '피폐한 삶', '자아의 버팀목', '자아에 대한 자각', '자아주체성 회복'을 포함하는 총5개의 주제를 추출했다. 둘째, 연구자들은 모든 주제들을 통합하여 '알코올중독자 여성배우자의 자아에 대한 자각을 통한 자아주체성 회복'이라는 본질적 주제를 뽑아냈다. 연구자들은 연구결과를 바탕으로 알코올중독자 여성배우자들에 대한 다양한 심리치료 시스템의 적용과 상담, 가족 및 신앙의 힘을 바탕으로 하는 자아버팀목에 관한 실천적 대안들을 제시했다.